Efeito do reforço teórico de anatomia na qualidade da escultura dental realizada por estudantes da pré-clínica - Azevedo, Renato Azevedo de (2014)
Knowledge of tooth anatomy is of great importance in the practice of dentistry, especially in oral rehabilitation. For the teeth to fulfill their functions, it is necessary that their anatomic shape is correct. This research aimed to evaluate the theoretical and practical knowledge of dental anatomy acquired by students of pre-clinical course regarding quality of anatomical restorations performed by these students before and after a didactic-theoretical reinforcement. For the evaluation of theoretical knowledge, a questionnaire with closed questions about dental anatomy was used. To evaluate the effect of didactic reinforcement on dental sculptures, two groups of 15 students from Pre-clinical were assessed. One group received tutoring on dental anatomy and the other did not. The assessment and comparison between the groups were made using a pre-determined score. The restorations were carried out in wax on artificial teeth from P-Occlusal. With the experimental results of the study, the comparison between the scores obtained on the sculptures for the two groups was performed using ANOVA. The Fisher exact test was used to compare the frequencies of correct answers in the questionnaires. For all analyzes was considered an α = 0.05. Stata 11 program was used for the analysis of the data. The theoretical evaluation revealed no significant difference (mean ± SD) between G1 (8.51 ± 0.66) and G2 (8.62 ± 0.91) in the notes previously obtained for this study (p = 0.725). In evaluating dental sculpture, all students of G1 showed an improvement in the quality of dental sculptures, and only in the tooth 42 there was no significant difference between groups (p = 0.096). The theoretical enhancement of dental anatomy promoted an improvement in student performance in dental carving of all teeth, but did not result in enhancing of knowledge about dental anatomy